A BIOCHEMICAL TEST FOR THE DISTINCTION OF FRESH FISH FROM FROZEN AND THAWED FISH - CHHATBAR, SUDHIR K; VELANKAR, N K (Fishery Technology, 2017)
It is observed that the freezing and thawing of fish leads to increase in the total activity of aspartate aminotransferase (AAT) in tissue finid due to the release of the bound form nf mitochondrial enzyme. Electrophoresis of the tissue fluid of fresh ur:frozen fish shows only a single fast-moving band of AAT in the anod:c region whereas frozen and thawed fish shows an additional slow-moving band corresponding to mitochondrial AAT in the cathodic region. The method can be adopted to distinguish fresh fish from frozen and thawed fish.